Research recast(ed): Following up with Dr. Erin Cowling - Ekelund, Brittany; Cave, Dylan; Cowling, Erin (My University, 2022)
Today we follow up on Dr. Erin Cowling’s research with Spanish theatre, including an exciting new foray into the subdiscipline of Siglo Latinx.
Keywords: Spanish theatre; Siglo Latinx; comedias